Pengaruh Testimoni Selebriti Terhadap Niat Beli Konsumen Generasi Z - Etty Zuliawati Zed; Adelia Putri Solekha; Diah Ayu Fatmawati; Elisa Nabila; Tithania Anzhani (CV. ULIL ALBAB CORP, 2024)
The digital era has transformed marketing strategies, especially through celebrity testimonials on social media platforms such as Instagram and TikTok. This study aims to analyze the influence of celebrity testimonials on the purchase intention of Generation Z. Data were collected via an online survey involving 300 respondents who are active social media users. Linear regression analysis was used to examine the relationship between the credibility of celebrity testimonials (trustworthiness, attractiveness, relevance) and purchase intention. The results are expected to show a significant influence of celebrity testimonials on the purchase decisions of Generation Z and provide practical insights for companies in designing celebrity endorsement-based marketing strategies.